Foreign direct investment and economic growth: the role of democracy - Ayub, Muhammad; Wan Ngah, Wan Azman Saini; Laila, Nisful; Mongid, Abdul; Wan Ismail, Wan Zulqurnain (Faculty of Economics and Management, Universiti Putra Malaysia, 2019)
This study investigates the growth-effect of foreign direct investment (FDI) in 67 developing countries covering from 1984 to 2016, with a special emphasis on the role of democracy. The empirical results obtained from generalized method of moments (GMM) estimation demonstrate that democracy plays a crucial role in moderating the positive effect of FDI on output growth. The results are robust to several alternative measures of democracy and FDI. This suggests that the marginal effect of FDI on growth depends on the level of democracy such that countries which promote democratic institution benefit more from FDI inflows. The finding is consistent with the growing view that the growth-effect of FDI depends on other intervening factors in the host countries.